The Effect of Organizational Commitment on Firm Performance: Intergenerational Differences - Muhammed Erdem Salamcı; Okşan Kibritci Artar (Journal of International Trade, Logistics and Law, 2021)
The main purpose of this research is to determine the effects of the sub-dimensions of organizational commitment (affective, continuance, and normative) on the concept of firm performance. Another aim of the study is to determine whether the sub-dimensions of organizational commitment differ in intergenerational. Within the scope of this aim, employees in banking sector were identified as “population”. This survey was applied to 209 employees in the banking sector in April 2021. Survey results were analyzed by the SPSS-20 program. As a result of the analysis, it was determined that affective commitment does not have a significant effect on firm performance. It has been shows that continuance commitment has a negative and significant effect on firm performance. Also, normative commitment has a positive and significant effect on firm performance. Finally, it was concluded that there was no difference in the affective commitment, continuance commitment, and normative commitment levels of bank employees belonging to the X and Y generations.